Open-Access Data: A key to sound agricultural policies and investments - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
On September 15-16, 2016, the Global Open Data for Agriculture & Nutrition (GODAN) Summit will be held in New York. GODAN is a rapidly growing group with 350 partners, including IFPRI, promoting collaboration to harness the growing volume of data to solve long-standing problems and to benefit farmers and the health of consumers. At the summit, IFPRI, the United States Department of Agriculture, and Syngenta will be hosting a side-event called Precision Agriculture that will assess how open data can enable emerging precision agriculture technologies across developed and developing regions.